Great expectations eaudiobook - Dickens, Charles (Recorded Books Inc., 1987)
Many people are put off by the sheer length of Charles Dickens' novels. Great Expectations is one of the most accessible of his works. If you've been unwilling to try Dickens before, this is the place to start! In what may be Dickens's best novel, humble, orphaned Pip is apprenticed to the dirty work of the forge but dares to dream of becoming a gentleman - and one day, under sudden and enigmatic circumstances, he finds himself in possession of "great expectations." In this gripping tale of crime and guilt, revenge and reward, the compelling characters include Magwitch, the fearful and fearsome convict; Estella, whose beauty is excelled only by her haughtiness; and the embittered Miss Havisham, an eccentric jilted bride